Comparative Evaluation of Botulinum Toxin Injection versus Topical Aluminum Chloride Hexahydrate 20% in Treatment of Axillary Hyperhidrosis - بدور رولا (Latakia University Journal -Medical Sciences Series, 2020)
Background: Axillary hyperhidrosis is a potential cause of severe physical and psychological distress. This study compares botulinum toxin versus topical aluminum chloride hexahydrate in treatment of axillary hyperhidrosis. Aim: To evaluate the efficacy and tolerance of botulinum toxin injection versus topical Aluminum chloride hexahydrate 20% in treatment of axillary hyperhidrosis. Methods: The study included 90 cases of axillary hyperhidrosis randomly allocated to 2 groups. One group was injected by botulinum toxin type A 100 units per axilla and the other group applied aluminum chloride hexahydrate 20% in roll. They were reviewed 2 weeks, 3 months, and 4 months later, improvement was evaluated using HDSS scale. Results: Botulinum therapy showed excellent improvement in the treatment of axillary hyperhidrosis aluminum chloride hexahydrate therapy showed significant improvement Conclusion: Better improvements were seen with botulinum therapy than with aluminum chloride hexahydrate therapy.